Teaching Pedagogies Used in Higher Education for Better Learning Outcomes - Gabrani, Goldie; Solomon, Andrew; Dviwedi, Utkarsh (Journal of Engineering Education Transformations, 2016)
There is a preconceived notion that a student and a teacher are two different entities, the one that gives is the teacher and the one that receives is the student. The fact that learning goes along with teaching and that there is teaching in learning is often discarded and has restricted the concept of education as a whole. Over time, changes have been made to the teaching and learning methodology, but never has it been freely dependent on the learner and the teacher, but also is affected by many factors which may or may not be in control of either of the two. The evolution of this process is destined to continue, but it is a matter of concern in which direction it grows. The gap between the student and the teacher is narrowing; the evolution of education has made making changes to the teaching pedagogy an optimized learning experience. With this in mind, there is a growing need for educationists to constantly make changes based on the requirement for an optimized learning experience. It is a two way effort to be made by both the teacher and the student alike, to create the closest to ideal space possible for a teaching learning environment.Moreover, today the world Is witnessing a rapid change in technology;hence it becomes completely necessary for both the student and the teacher alike to keep themselves updated. This paper is aimed to exhibit some of the contemporary practices being implemented in the teaching methodology to make the learning experience better. Various innovative methodologies that have been implemented are discussed. The effect of implementing these ideologies on both teaching and learning experiences alike without the general gloomy perception of a class room is studied.